Ecology as a integral discipline to address socio-environmental conflicts - Marelli, Silvia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In 1888 Ernest Haeckel defined ecology as a science that studies the relationship between organisms, and later, in the same work, as "the science of organisms relations with their outside world." This work is intended to reflect ecology as a holistic discipline that allows us to integrate tools from sociology, statistics, cartography, chemistry among others to address environmental conflicts of different kinds. The experiences that have been carried out within their students' thesis projects of the Degree in Ecology and Conservation of the Environment of the National University of Santiago del Estero will be briefly underilized. These projects are preceded by volunteer experiences and/or research scholarships. These previous experiences allow the student to identify conflicts and improve the handling of tools to treat the problems identified. In the first instance I will present two degree thesis projects linked to the problem of deforestation and peasant movements of the interior of the province. Later I will emphasize urban ecology as a guiding discipline to carry out my degree research project linked to the quality of ecosystem services in urban environments and my doctoral research project that has as its central themes to waste management and recuperators urban in the capital city of Santiago del Estero.